Clay funerary figurines from tombs MMA 1151 and MMA 1152 in Sheikh Abd el-Gurna - Marta Kaczanowicz (Polish Archaeology in the Mediterranean, 2018)
A significant number of clay ushebtis comes from two Middle Kingdom tombs MMA 1151 and 1152 investigated by a Polish team in Western Thebes. The funerary figurines belong to a later phase of tomb reuse in the first millennium BC. Nine types were distinguished: six of baked clay and three of unbaked clay. The types and their distribution in the Theban necropolis are discussed in this paper, including the implications of these findings for the debate on the existence of workshops manufacturing funerary goods in Thebes